Play and Learn with Tradisional Local Wisdom Game in School - Nurul Anam; Naily Inayatul Maghfirah; Saiyenah Saiyenah (Nurul Jadid University, 2022)
In Indonesia, the number of online game addicted in children was experienting a very dangerous development. One doctor predicted that the highers number of online game addicted was Asia. This is very ironic. Since the first, the Indonesian nation has had many traditional games that can be used in learning activities at school. This traditional game was very beneficial for the development of children's abilities, especially children's motoric skills. In the midst of the dangers of massive online games, the RA Nurul Ulum educational institution in Sumbersalak Village used traditional local wisdom game methods and media in every learning activity. This was done so that the students continue to love and preserve the educational games of traditional local wisdom. From this background, this study aims at describing the application of traditional games in improving the gross motoric skills of early childhood in RA. The research method used was a descriptive qualitative approach. The results of the research show that the traditional local wisdom games used are engklek and jumping rope games. The application of this game can improve gross motoric skills in early childhood, stimulated children in developing cooperation, make children more creative, active, adept at jumping, jumping and being responsible in a game. From the application of this traditional game, children's gross motoric skills developed more rapidly and children get to know traditional games and their types.